Crosstalk of TGF-β and somatostatin signaling in adenocarcinoma and neuroendocrine tumors of the pancreas: a brief review - Ungefroren, Hendrik; Randeva, Harpal; Lehnert, Hendrik; Schrader, Jörg; Marquardt, Jens-Uwe; Konukiewitz, Björn; Hass, Ralf (Frontiers in Endocrinology, 2025)
Although the vast majority of cancers affecting the human pancreas are pancreatic ductal adenocarcinomas (PDAC), there are several other cancer types originating from non-exocrine cells of this organ, i.e., pancreatic neuroendocrine tumors (panNET). Genomic analyses of PDAC and panNET revealed that certain signaling pathways such as those triggered by transforming growth factor-β (TGF-β) are frequently altered, highlighting their crucial role in pancreatic tumor development. In PDAC, TGF-β plays a dual role acting as a tumor suppressor in healthy tissue and early stages of tumor development but as a promoter of tumor progression in later stages. This peptide growth factor acts as a potent inducer of epithelial-to-mesenchymal transition (EMT), a developmental program that transforms otherwise stationary epithelial cells to invasive mesenchymal cells with enhanced metastatic potential. TGF-β signals through both the canonical Smad pathway involving the receptor-regulated Smad proteins, SMAD2 and SMAD3, and the common-mediator Smad, SMAD4, as well as Smad-independent pathways, i.e., ERK1/2, PI3K/AKT, and somatostatin (SST). Accumulating evidence indicates an intimate crosstalk between TGF-β and SST signaling, not only in PDAC but, more recently, also in panNET. In this work, we review the available evidence on signaling interactions between both pathways, which we believe are of potential but as yet insufficiently appreciated importance for pancreatic cancer development and/or progression as well as novel therapeutic approaches.